Dengue Fever: Features and outcome among Pediatric patients (Journal of Dhaka National Medical College & Hospital, 2019)
Background: The gradual increase of Dengue fever among children of our country is a growing challenge of child health. Dengue fever causes considerable morbidity and mortality and a leading cause of hospitalisation during its outbreak. Therefore we aimed at a study of features and outcome of Dengue fever among children admitted in our hospital.Objectives: The objective of the study was to study the features and outcome of Dengue viral illness for better understanding and efficient management of the disease for improvement of child health service.Materials and methods: Between 4th September to 26th December 2018, we conducted this study among children admitted in Pediatric ward of Dhaka National Medical College Hospital. Diagnosis was established by careful history taking, Physical examination and suitable laboratory investigations. Clinical features, laboratory findings and treatment outcome were studied and subsequent statistical significance was analyzed.Results: Out of 108 study patients, 3 (2.78%) were 5 days in 39.81%, 33 children had fever